Role of the Aryl Hydrocarbon Receptor and Gut Microbiota-Derived Metabolites Indole-3-Acetic Acid in Sulforaphane Alleviates Hepatic Steatosis in Mice - Xu, Xiuxiu; Sun, Siyuan; Liang, Ling; Lou, Chenxi; He, Qijin; Ran, Maojuan; Zhang, Lu; Zhang, Jingyue; Yan, Chen; Yuan, Hengjie; Zhou, Lu; Chen, Xin; et al. (Frontiers in Nutrition, 2021)
Scope: Gut microbiome-derived metabolites are the major mediators of diet-induced host-microbial interactions. Aryl hydrocarbon receptor (AHR) plays a crucial role in glucose, lipid, and cholesterol metabolism in the liver. In this study, we aimed to investigate the role of indole-3-acetic acid (IAA) and AHR in sulforaphane (SFN) alleviates hepatic steatosis in mice fed on a high-fat diet (HFD). Methods and Results: The HFD-fed male C57BL/6 mice were intervened with SFN for 6 weeks. HFD-mice showed classical pathophysiological characteristics of hepatic steatosis. The results showed that SFN significantly reduced body weight, liver inflammation and hepatic steatosis in HFD-fed mice. SFN reduced hepatic lipogenesis by activating AHR/SREBP-1C pathway, which was confirmed in HepG2 cell experiments. Moreover, SFN increased hepatic antioxidant activity by modulating Nrf-2/NQO1 expression. SFN increased serum and liver IAA level in HFD mice. Notably, SFN manipulated the gut microbiota, resulting in reducing Deferribacteres and proportions of the phylum Firmicutes/Bacteroidetes and increasing the abundance of specific bacteria that produce IAA. Furthermore, SFN upregulated Ahr expression and decreased the expression of inflammatory cytokines in Raw264.7 cells. Conclusions: SFN ameliorated hepatic steatosis not only by modulating lipid metabolism via AHR/SREBP-1C pathway but regulating IAA and gut microbiota in HFD-induced NAFLD mice.